ANALISIS DANA PIHAK KETIGA DAN KREDIT BERMASALAH TERHADAP TINGKAT PROFITABILITAS PADA INDUSTRI PERBANKAN DI BURSA EFEK INDONESIA - Rudy - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2013)
Bank funds which can be obtained from the bank's own capital from shareholders, fromother agencies and from the public in the form of demand deposits, savings deposits and the socalled third party funds. Funds collected are allocated in order to achieve profitability and maintainsufficient liquidity position remains secureThe high non-performing loans due to credit expansion undertaken in the past are moreconcentrated in the property sector, giving rise to the growth of non-performing loans.To survive, the banks have to raise the level of profitability. Profitability describes the ability of thebanking companies to profit through all of the capabilities and resources. The results of the analysisobtained by partial LDR variables have a significant effect on the profitability of the banking industryand the partial NPL variable has no significant effect on profitability.